Wide-bandgap semiconductor based power converters for renewable energy systems - Gurpinar, Emre (2017)
The demand for low carbon economy and limited fossil resources for energy generation drives the research on renewable energy sources and the key technology for utilisation of renewable energy sources: power electronics. Innovative inverter topologies and emerging WBG semiconductor based devices at 600 V blocking class are the enabling technologies for more efficient, reliable and accessible photovoltaic based electricity generation.